Business incubators role in fostering entrepreneurship: A comprehensive review of entrepreneurs’ selection process - Belhaj, Fozi Ali (Edelweiss Applied Science and Technology, 2025)
The study aims to review the status and an effective selection process of entrepreneurs from business incubators in Hadhramout, Yemen, as the most important process that primarily aims to investigate the innovative and creative ideas that orient small and medium-scale enterprises desirous of commercializing R&D results, especially from the research institutions, with a view to promoting innovation and entrepreneurship development. The study adopted a combination method of observing the status of the business incubators and conducting unstructured interviews with the educational institutions’ managers who provide entrepreneurship programs. The study’s results found that business incubators have a significant contribution to fostering entrepreneurship in the Yemeni business environment and also revealed that the steps and practices followed to select entrepreneurs play a major role in enhancing benefits and reducing the costs of the entrepreneurs’ process. Theoretically, the study contributes to improving understanding of business incubators and introduces an effective process to select entrepreneurs. In addition, it reviews the role of business incubators in fostering entrepreneurship. The study also presents a practical contribution to public and private leaders to raise awareness of the importance of business incubators for promoting entrepreneurship at the small and medium enterprise level around the world.